Catalyst for photocatalytic oxidation of isoprene and its application
By using photocatalytic oxidation technology using nano-titanium dioxide, carbon quantum dot-modified titanium dioxide and ceria as catalysts, the problem of ozone and secondary organic aerosol pollution caused by isoprene emissions from plants has been solved, and the isoprene production has been achieved. Efficient degradation and carbon dioxide generation.
Patent Information
- Application Number
- CN202310265863.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The prior art has not yet developed an effective pollution control method to treat isoprene emitted by plants, resulting in the production of pollutants such as ozone and secondary organic aerosols in the atmosphere.
Nanoscale titanium dioxide, carbon quantum dot modified titanium dioxide and ceria are used as catalysts to oxidize isoprene in the atmosphere into carbon dioxide through photocatalytic oxidation technology to avoid the generation of pollutants.
It achieves effective photocatalytic degradation of isoprene emitted from the atmospheric environment and plants, avoids the generation of pollutants such as ozone and secondary organic aerosols in the atmosphere, and has good applicability and environmental friendliness.
Smart Images

Figure CN116078367B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, and in particular to a catalyst for photocatalytic oxidation of isoprene and application thereof. Background Art
[0002] Isoprene is the plant-derived volatile organic compound with the highest global emission, with an annual emission of up to 600 Tg, accounting for 40% of global non-methane biogenic emissions, and is one of the most important non-methane hydrocarbons in the troposphere. Isoprene is a reactive olefin that can be oxidized by hydroxyl radicals (OH), nitrate radicals (NO3), ozone radicals (O3) and halogen radicals in the atmosphere to produce volatile organic compounds with a higher degree of oxidation, and it makes an important contribution to regional ozone pollution and organic aerosol formation.
[0003] Studies have shown that in the summer in the North China Plain, the Yangtze River Delta and the Pearl River Delta in China, the contribution of plant-derived isoprene to ozone generation potential ranks among the top; isoprene has also been found to be the main source of summer ozone in Europe, North America and other places. Although the concentration of isoprene in the atmosphere is low, due to its large emissions and high activity, choosing a fast and effective method to remove isoprene emitted by plants in the atmosphere without causing secondary pollution has become a difficult problem in the field of atmospheric environment. So far, research on isoprene at home and abroad has mainly focused on the study of atmospheric environmental behavior, explaining its heterogeneous reactions, adsorption on particulate matter, and interactions with metal oxide cluster molecules from the perspective of atmospheric chemistry. At present, there is no pollution control technology for isoprene emitted by the atmospheric environment and plants. Summary of the invention
[0004] In view of the above-mentioned technical problems existing in the prior art, the present invention provides a catalyst for the photocatalytic oxidation of isoprene and its application. The isoprene emitted from the atmospheric environment and plants is photocatalytically oxidized by the catalyst to be oxidized into carbon dioxide, thereby avoiding the generation of pollutants by isoprene in the atmosphere.
[0005] The invention discloses a catalyst for photocatalytic oxidation of isoprene. The catalyst is used for photocatalytic degradation of isoprene. The catalyst comprises any one of the following compounds or a combination thereof: nano titanium dioxide, carbon quantum dot-modified titanium dioxide and nano cerium dioxide.
[0006] Preferably, the nano titanium dioxide includes P25 type titanium dioxide or titanium dioxide prepared by sol-gel method;
[0007] The sol-gel method comprises:
[0008] dissolving isopropyl titanate in ethanol to obtain a first mixed solution;
[0009] Add nitric acid at a volume ratio of 1:50 dropwise into the first mixed solution and stir to obtain a sol;
[0010] The sol is dried and calcined to obtain titanium dioxide powder prepared by a sol-gel method.
[0011] Specifically, the method for preparing titanium dioxide by the sol-gel method includes:
[0012] Dissolve 4 ml of isopropyl titanate in 20 ml of anhydrous ethanol to obtain a first mixed solution;
[0013] 150 ml of nitric acid with a volume ratio of 1:50 was dropped into the first mixed solution, and the temperature was kept at 60° C. and stirred during the dropping process to obtain a sol;
[0014] After 1-3 hours, the sol is dried at 90-100° C. and then calcined at 350-400° C. for 1-3 hours to obtain titanium dioxide powder prepared by the sol-gel method.
[0015] Preferably, the preparation method of carbon quantum dot modified titanium dioxide comprises:
[0016] Dissolve urea and citric acid in water, and perform hydrothermal reaction at 150-180° C. for 3-8 hours to obtain a second mixed solution;
[0017] After cooling, large particles in the second mixed solution are removed by centrifugation;
[0018] After removing large particles, drying is performed to obtain carbon quantum dots;
[0019] dissolving nano-titanium dioxide powder in ethanol to obtain a suspension;
[0020] Adding the carbon quantum dots into the suspension and mixing them to obtain a third mixed solution;
[0021] The third mixed liquid is dried and then calcined to obtain carbon quantum dot-modified titanium dioxide.
[0022] Specifically, the preparation method of carbon quantum dot modified titanium dioxide includes:
[0023] Dissolve 1 gram of urea and 1 gram of citric acid in 15 ml of water, stir well, and perform hydrothermal reaction at 150-180° C. for 6 hours to obtain a second mixed solution;
[0024] After cooling, large particles in the second mixed solution were removed by centrifugation at 12000 r / m for 20 minutes;
[0025] After removing the large particles, the remaining solution was dried at 80°C to obtain carbon quantum dots;
[0026] Dissolve 0.5 g of nano titanium dioxide powder in 30 ml of ethanol to obtain a suspension, and mix thoroughly;
[0027] Adding the carbon quantum dots into the suspension and mixing thoroughly to obtain a third mixed solution;
[0028] The third mixed solution was evaporated to dryness at 75° C., and then calcined at 300° C. for 3 h to obtain carbon quantum dot-modified titanium dioxide.
[0029] Preferably, the preparation method of cerium dioxide comprises:
[0030] Adding citric acid to the Ce(NO3)3 solution to obtain a fourth mixed solution;
[0031] Maintaining the fourth mixed solution at 80-90° C. until a yellow gel is obtained;
[0032] The yellow gel is dried at 90-110° C. and then calcined at 300-400° C. for 2-5 hours to obtain cerium dioxide.
[0033] Specifically, the preparation method of cerium dioxide includes:
[0034] After adding Ce(NO3)3·6H2O to 120 mL of deionized water, stirring, citric acid was added to obtain a fourth mixed solution, wherein the molar ratio of Ce to citric acid was 1:1;
[0035] The fourth mixed solution is maintained at 90° C., and as the excess water in the solution gradually evaporates, a yellow gel is obtained;
[0036] The yellow gel was dried at 110° C. and then calcined at 400° C. for 3 hours to obtain cerium dioxide.
[0037] The present invention also provides a method for photocatalytic degradation of isoprene, the method comprising the following steps:
[0038] dispersing the catalyst in water by ultrasonication to obtain a fifth mixed solution;
[0039] Spraying, coating, smearing or pouring the fifth mixed liquid onto the surface of the medium;
[0040] After drying, isoprene is photocatalytically degraded by the catalyst on the surface of the medium.
[0041] Preferably, the medium includes: a metal plate, plant leaves, tree trunks, building surfaces or land;
[0042] The wavelength range of the light source for photocatalysis is 350-760 nm; the relative humidity for photocatalysis is 20% and the temperature is 25°C.
[0043] Preferably, the thickness of the catalyst in the surface interface is 32.5-65 microns.
[0044] Compared with the prior art, the present invention has the following beneficial effects: the catalyst photocatalytically degrades isoprene emitted from the atmosphere and plants, oxidizes it into carbon dioxide, and avoids the generation of pollutants from isoprene in the atmosphere. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is an analysis chart of the photocatalytic degradation activity of P25 titanium dioxide on isoprene at different temperatures.
[0046] Figure 2 This is an analysis chart of the photocatalytic degradation activity of P25 type titanium dioxide on isoprene at different humidity levels.
[0047] Figure 3 This is an activity analysis diagram of different masses of P25 titanium dioxide on the photocatalytic degradation of isoprene.
[0048] Figure 4 This is an analysis of the photocatalytic degradation activity and carbon dioxide selectivity of P25 titanium dioxide for isoprene under different light sources;
[0049] Figure 5 is a flow chart of a method for photocatalytic degradation of isoprene. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0052] A catalyst for photocatalytic oxidation of isoprene. The catalyst is used for photocatalytic degradation of isoprene. The catalyst comprises any one of the following compounds or a combination thereof: nano titanium dioxide, carbon quantum dot-modified titanium dioxide and cerium dioxide.
[0053] The catalyst photocatalytically degrades isoprene emitted from the atmosphere and plants, oxidizing it into carbon dioxide to avoid isoprene from generating secondary pollutants such as ozone and secondary organic aerosols in the atmosphere. For example, the catalyst is dispersed in the surface interface of the medium, and the isoprene emitted from the atmosphere and plants is photocatalytically degraded by the catalyst in the surface interface. The medium includes: a metal plate, plant leaves, tree trunks, building surfaces or land.
[0054] Wherein, the nano titanium dioxide includes P25 type titanium dioxide or titanium dioxide prepared by sol-gel method.
[0055] like Figure 5 As shown, the method for photocatalytic oxidation and degradation of isoprene using a catalyst includes:
[0056] Step S1: dispersing the catalyst in water by ultrasound to obtain a fifth mixed solution.
[0057] Step S2: Spray, coat, apply or pour the fifth mixed liquid onto the surface of the medium.
[0058] Step S3: After drying, photocatalytic degradation of isoprene is carried out through the catalyst on the surface of the medium.
[0059] Example 1
[0060] Using P25 titanium dioxide as a catalyst, the photocatalytic degradation experiment of isoprene was carried out under the flow system of the laboratory, and the degradation effect of isoprene under different temperatures, humidity, light source types and catalyst quality was tested. Low-concentration isoprene gas (the concentration was controlled at 650ppb) was introduced into the reaction system with a residence time of 1.36s. The signal intensity of isoprene during the reaction and the concentration of product CO2 were detected by single photon ionization source mass spectrometry (SPIMS-3000) and greenhouse gas analyzer (Picarro). A quartz skylight was set on the top of the reaction system, and a xenon lamp light source was used for vertical irradiation to ensure that the catalyst was fully exposed to light.
[0061] 0.02 g of P25 powder was weighed and ultrasonically dispersed in 5 mL of deionized water, poured onto a stainless steel disc (5.5 cm in diameter), and then placed in a forced air drying oven and dried at 80°C, thereby evenly coating the disc with P25 to obtain a reaction medium. The reaction medium simulates the situation where the catalyst is coated on the surface of a medium such as a plant leaf.
[0062] Condition 1: Effect of temperature on photocatalytic degradation
[0063] The activity of P25 titanium dioxide on the photocatalytic degradation of isoprene at different temperatures was tested. Specifically, the temperature of the reaction system was controlled by a water bath, and the water bath temperatures were set to 25°C, 35°C, 40°C and 70°C, respectively, and irradiated with a light source of the same wavelength (wavelength of 350-760nm). The activity of P25 titanium dioxide on the photocatalytic degradation of isoprene at different temperatures was measured, such as Figure 1 As shown, the isoprene conversion rate / degradation rate is higher at 25°C, but overall the effect of temperature on the degradation of isoprene is small.
[0064] Condition 2: Effect of humidity on photocatalytic degradation
[0065] A humidifier was set up to control the reaction humidity by adjusting the proportion of the atmosphere purged with liquid water. The conversion results were tested at room temperature (25°C) with humidity of 0%, 20%, 50% and 80%. The conditions such as catalyst dosage and light source were consistent with condition 1. The results are shown in Figure 1. Figure 2 As shown, the conversion rate is better when the humidity is 20%, but overall the effect of humidity on the photocatalytic degradation of isoprene is not significant.
[0066] Condition 3: Effect of catalyst thickness on photocatalytic degradation
[0067] The effect of different masses of P25 titanium dioxide on the photocatalytic degradation activity of isoprene was detected. The mass of the catalyst affects the thickness of the coated catalyst, which in turn affects the adsorption of isoprene by the catalyst. According to the mass of the catalyst, it is divided into three groups: 0.01g group, 0.02g group, and 0.05g group. The diameter of the disc is 5.5cm. It is calculated that the catalyst thickness of the 0.01g group is 32.5 microns; the catalyst thickness of the 0.02g group is 65 microns; and the catalyst thickness of the 0.05g group is 162.5 microns. The environmental humidity is controlled to 0, and the wavelength of the light source is 200-400nm. The results are as follows Figure 3 As shown, it can be seen that the quality of the catalyst has a certain effect on the photocatalytic degradation of isoprene, and 0.02g of catalyst has the best degradation effect on isoprene.
[0068] Condition 4: Effect of light source wavelength on photocatalytic degradation
[0069] Based on the optimal experimental conditions obtained under the above conditions, the conversion rate of isoprene and CO2 selectivity under different light sources were further tested. Filters were installed to provide light of different wavelengths, with the wavelength of ultraviolet light being 200-400nm, the wavelength of ultraviolet-visible light being 350-760nm, and the wavelength of visible light being 400-760nm. The light intensities in the ultraviolet and visible regions were 63.9 and 456.8 mW cm, respectively. -2 . Under the irradiation of ultraviolet light, ultraviolet-visible light and visible light, such as Figure 4, the conversion rates of isoprene were 56.6%, 44.1% and 20.4%, and the corresponding CO2 selectivities were 71.8%, 84.3% and 24.2%, respectively. The photocatalytic effect was better under UV light or UV-visible light, while under visible light irradiation, the conversion rate of isoprene and the selectivity of CO2 were poor. Under visible light irradiation with lower energy, fewer photogenerated carriers were generated, so the catalytic effect was poor.
[0070] The photocatalytic degradation of isoprene was carried out by using P25 type titanium dioxide, and a good degradation effect was obtained, which can overcome the influence of environmental factors and has good applicability.
[0071] Example 2
[0072] Titanium dioxide prepared by sol-gel method. The preparation method uses isopropyl titanate as a precursor and adopts a heat-assisted sol-gel method to prepare: 4 ml of isopropyl titanate is dissolved in 20 ml of anhydrous ethanol to obtain a first mixed solution; 150 ml of nitric acid with a volume ratio of 1:50 is dripped into the first mixed solution, and the temperature is maintained at 60°C and stirred during the dripping process to obtain a sol; after 2 hours, the sol is dried at 100°C and calcined at 400°C for 2 hours to obtain titanium dioxide powder prepared by the sol-gel method.
[0073] Titanium dioxide exists in three crystal phases: anatase, rutile and brookite. During preparation, it can form a mixed crystal structure, which is beneficial to the separation of photogenerated electrons and holes and has excellent photocatalytic ability.
[0074] Example 3
[0075] Preparation of modified titanium dioxide. The preparation method of carbon quantum dot modified titanium dioxide includes:
[0076] Dissolve 1 gram of urea and 1 gram of citric acid in 15 ml of water, stir well, and perform hydrothermal reaction at 180°C for 6 hours to obtain a second mixed solution; after cooling, remove large particles in the second mixed solution by centrifugation at 12000r / m for 20 minutes; after removing the large particles, dry the remaining solution at 80°C to obtain carbon quantum dots; dissolve 0.5 g of nano titanium dioxide powder in 30 ml of ethanol to obtain a suspension, and mix well; add the carbon quantum dots to the suspension, mix well, and obtain a third mixed solution; evaporate the third mixed solution at 75°C to dryness, and calcine at 300°C for 3 hours to obtain carbon quantum dot-modified titanium dioxide.
[0077] Specifically, 5 wt% carbon quantum dots-P25 type titanium dioxide and 5 wt% carbon quantum dots-sol-gel method titanium dioxide were prepared.
[0078] Example 4
[0079] The sol-gel method is used to prepare cerium dioxide as a catalyst. The preparation method of cerium dioxide includes: adding Ce(NO3)3·6H2O to 120mL of deionized water, stirring and adding citric acid to obtain a fourth mixed solution, wherein the molar ratio of Ce to citric acid is 1:1; maintaining the fourth mixed solution at 90°C, and gradually evaporating the excess water in the solution to obtain a yellow gel; drying the yellow gel at 110°C, and calcining at 400°C for 3 hours to obtain cerium dioxide.
[0080] 0.02 g of the above catalysts were used to prepare disks, respectively, and the photocatalytic degradation of isoprene was carried out. The test results are shown in Table 1. In the photocatalytic process, the reaction was controlled under the conditions of an initial isoprene concentration of 650 ppb, a residence time of 1.36 s, room temperature, and dryness.
[0081] Table 1
[0082]
[0083] Comparing experiments 1 and 2, it can be seen that the isoprene removal rate and CO2 selectivity at a wavelength of 350-760nm are significantly improved, and it can be seen that ultraviolet light has a greater impact on photocatalytic efficiency; comparing experiments 1 and 3, it can be seen that the isoprene removal rate of titanium dioxide prepared by the sol-gel method is improved; comparing experiments 2, 4 and 5, it can be seen that carbon quantum dot-modified titanium dioxide greatly improves the isoprene removal rate and CO2 selectivity in visible light, which is conducive to the efficient use of sunlight. The catalysts used all showed good degradation effects under laboratory conditions and have good applicability.
[0084] The catalyst of the present invention is low-cost, highly stable and non-toxic, and can be used for photocatalytic removal of isoprene emitted from the atmosphere and plants by foliar spraying and surface spraying, and oxidizing it into carbon dioxide to avoid the generation of pollutants such as ozone and secondary organic aerosols through photochemical reactions in the atmosphere.
[0085] Therefore, it is feasible to use the catalyst for the photocatalytic degradation of isoprene emitted from the atmosphere and plants. The required light source is provided by sunlight, so that the isoprene released from the plant leaves can be photocatalytically degraded in a timely manner. The sprayed / sprayed catalyst will be evenly attached to the plant leaves, fully contact with isoprene, and uniformly irradiated by sunlight, thereby achieving low energy consumption and high activity degradation. In practical applications, the catalyst solution can be sprayed over the forest by drone to achieve the control of forest-derived isoprene.
[0086] The present invention adopts photocatalytic oxidation technology, does not require heating or power supply, and still has a certain active response within the visible light range, which is beneficial to the effective use of sunlight; the isoprene emitted by plants can be directly contacted with the catalyst by spraying on the leaf surface or the environmental interface, and then mainly catalytically oxidized to carbon dioxide under the irradiation of sunlight, so it is suitable for the reaction system of degrading low-concentration isoprene emitted by plants in the atmosphere, reducing its contribution to ozone and secondary aerosol pollution; carbon quantum dot-modified titanium dioxide broadens the absorption range of visible light, which is beneficial to improving the photocatalytic performance under visible light; at different temperatures and humidities, the catalyst shows good catalytic activity, indicating that the invention has strong application applicability, is not very demanding on the environment, and has high practical value.
[0087] It should be pointed out that the catalyst is not limited to titanium dioxide, carbon quantum dot-modified titanium dioxide and ceria, and titanium dioxide and ceria materials prepared by other methods can also be used for the photocatalytic removal of isoprene.
[0088] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An application of a carbon quantum dot modified titanium dioxide catalyst, characterized in that: The catalyst is used for the photocatalytic oxidation of isoprene, and the photocatalytic oxidation method comprises the following steps: dispersing the catalyst in water by ultrasound to obtain a fifth mixed solution; Spraying, coating, smearing or pouring the fifth mixed liquid onto the surface of the medium; After drying, isoprene is photocatalytically oxidized by the catalyst on the surface of the medium.
2. The use according to claim 1, characterized in that: The medium includes: a metal plate, plant leaves, tree trunks, building surfaces or land; The wavelength range of the light source for photocatalysis is 350-760 nm; the relative humidity for photocatalysis is 20% and the temperature is 25°C.
3. The use according to claim 1, characterized in that: The thickness of the catalyst in the medium surface interface is: 32.5-65 microns.
4. The use according to claim 1, characterized in that: The preparation method of carbon quantum dot modified titanium dioxide comprises: Dissolve urea and citric acid in water, and perform hydrothermal reaction at 150-180° C. for 3-8 hours to obtain a second mixed solution; After cooling, large particles in the second mixed solution are removed by centrifugation; After removing large particles, drying is performed to obtain carbon quantum dots; dissolving nano-titanium dioxide powder in ethanol to obtain a suspension; Adding the carbon quantum dots into the suspension and mixing them to obtain a third mixed solution; The third mixed liquid is dried and then calcined to obtain carbon quantum dot-modified titanium dioxide.
5. The use according to claim 4, characterized in that: The specific preparation method of carbon quantum dot modified titanium dioxide includes: Dissolve 1 gram of urea and 1 gram of citric acid in 15 ml of water, stir well, and perform hydrothermal reaction at 150-180° C. for 6 hours to obtain a second mixed solution; After cooling, large particles in the second mixed solution were removed by centrifugation at 12000 r / m for 20 min; After removing the large particles, the remaining solution was dried at 80°C to obtain carbon quantum dots; Dissolve 0.5 g of nano titanium dioxide powder in 30 ml of ethanol to obtain a suspension, and mix thoroughly; Adding the carbon quantum dots into the suspension and mixing thoroughly to obtain a third mixed solution; The third mixed solution was evaporated to dryness at 75° C., and then calcined at 300° C. for 3 hours to obtain carbon quantum dot-modified titanium dioxide.
Citation Information
Patent Citations
Nano molecular sieve plate type VOC purifier
CN110064274A